2011
DOI: 10.1038/ejhg.2010.234
|View full text |Cite
|
Sign up to set email alerts
|

Bohring–Opitz (Oberklaid–Danks) syndrome: clinical study, review of the literature, and discussion of possible pathogenesis

Abstract: Bohring-Opitz syndrome (BOS) is a rare congenital disorder of unknown etiology diagnosed on the basis of distinctive clinical features. We suggest diagnostic criteria for this condition, describe ten previously unreported patients, and update the natural history of four previously reported patients. This is the largest series reported to date, providing a unique opportunity to document the key clinical features and course through childhood. Investigations undertaken to try and elucidate the underlying pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 10 publications
1
61
0
1
Order By: Relevance
“…Our case clearly fulfilled the clinical criteria of BOPS established by Hastings et al (2011), and had a novel disease-causing variant in the ASXL1 gene, and yet showed two atypical features. The fist and head size in our proband was normal, which is contrary to microcephaly reported in every case with ASXL1 disease- causing variants (Dangiolo et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our case clearly fulfilled the clinical criteria of BOPS established by Hastings et al (2011), and had a novel disease-causing variant in the ASXL1 gene, and yet showed two atypical features. The fist and head size in our proband was normal, which is contrary to microcephaly reported in every case with ASXL1 disease- causing variants (Dangiolo et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
“…The majority of these cases were considered to have Bohring-Opitz syndrome (BOPS) as they fulfilled the clinical diagnostic criteria established by Hastings et al (2011); however, only a minority have a confirmed molecular diagnosis to date. Hoischen et al (2011) used exome sequencing in three classical BOPS cases with a similar phenotype to find heterozygous denovo nonsense mutations in the ASXL1 (additional sex combs-like transcriptional regulator 1) gene to be responsible for BOPS when the traditional methods had failed to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in most individuals, an ulnar deviation of the hands was observed at younger age which was, however, mild and not comparable to the typical BOPS posture. [3][4][5] Bainbridge et al 2 as well as Dinwiddie et al 2,10 postulated that their patients carrying an ASXL3 mutation resembled those with BOPS (also reviewed by Russell and Graham), 17 as they showed clinical overlap with severe feeding difficulties (4/5), neurological abnormalities with significant DD (5/5), small birth measurements (2/4) and microcephaly (3/4). The same findings were observed in the girl reported by Hori et al, 12 but especially because of the typical posture being absent, her phenotype was evaluated as distinct from those in BOPS.…”
Section: Clinical Characterization Of Patients With Asxl3 Lof Variantsmentioning
confidence: 99%
“…BOPS is a severe developmental disorder mainly characterized by intrauterine growth retardation, severe DD and ID, feeding difficulties (often requiring tube feeding), failure to thrive, microcephaly, a specific craniofacial phenotype with trigonocephaly, exophthalmus, nevus flammeus of the forehead, upslanting palpebral fissures and a peculiar posture of the arms (known as 'BOPS posture') with flexion of elbow and wrist, ulnar deviation of the wrist and of the metacarpophalangeal joints. [3][4][5] In 2011, germline mutations in ASXL1 (MIM *612990) were shown to be causative for Bohring-Opitz syndrome. 6 ASXL3 and ASXL1 belong to the same gene family.…”
Section: Introductionmentioning
confidence: 99%
“…El fenotipo sutil y variable deriva en que el diagnóstico se establece con la secuenciación completa del genoma o del exoma 3,[8][9][10][11] . Las características clíni-cas comunes, retraso psicomotor grave, dismorfias faciales, falla del crecimiento y dificultades para la alimentación se confunden con otros síndromes como el síndrome de Bohring-Opitz (BOS, MIM # 605039) (tabla 1) 12,13 . El BOS se asocia a variantes génicas en ASXL1 y no se han detectado variantes en ASXL3 por lo que se considera que estos sín-dromes pudieran ser 2 entidades distintas 3,12 .…”
unclassified